Alkyl Substituted Effects on Carbenes: DFT ab initio Calculations - REZAIE ROD, A.; VESSALLY, E. (Asian Journal of Chemistry, 2010)
Full geometry optimizations are carried out on alkyl substituted acyclic carbene by B3LYP method using 6-311++G** basis set of the Gaussian 98 system of program. For methylene (CH2) and ethylidene (CH3CH), the triplet state is ground state while for propylidene and other large substituted acyclic carbenes, the singlet state is ground state. By comparing NBO charges on methylenic carbon of CH2 and other large substituted acyclic carbenes, the role of methyl group is electron withdrawing more than hydrogen atom. Higher electronegatively of methyl group leads to stabilize the singlet respect to triplet state as well as decreasing the singlettriplet splitting energies.